Short communication. Partial resistance of a cotton mutant to Cotton leaf curl Burewala virus - Akhtar, K. P.; Khan, M. K. R.; Ahmad, M.; Sarwar, N.; Ditta, A. (Spanish Journal of Agricultural Research, 2010)
Cotton leaf curl disease (CLCuD), caused by Cotton leaf curl Burewala virus (CLCuBV), is a major constraint for a successful production of cotton in Pakistan. All the available cotton cultivars are susceptible to this virus. Breeding for resistance to CLCuBV is the best tactic to reduce economic losses caused by this virus. In the absence of a resistant source the present investigations were carried out to find out CLCuBV-resistant genotypes by mutagenization. NIAB-111 (female parent) was crossed separately with two male parents, NIAB-999 and CIM-499. The resulting F1 seeds were gamma irradiated. Resistance to CLCuBV was evaluated by visual symptom scoring in the field conditions and in nethouse/greenhouse using whitefly and graft inoculations. Out of 20 mutants tested in M5 generation, one, mutant M-112-59/22 showed partial resistance to CLCuBV, as concluded from its low severity index (SI) of 2.3 and percent disease index (PDI) of 20. M-112-59/22 consistently expressed resistance to CLCuBV in the normal cotton growing season, while it showed a more moderate resistance response when sown late in the field, or under greenhouse conditions following inoculation by whiteflies (SI = 3.3) or graft inoculation (SI= 3.4). The yield per plant of M-112-59/22 was higher than its parents with desirable fiber characteristics even under conducive disease development conditions. These results show that mutant M-112-59/22 is a CLCuBV partially resistant source when yield, fiber quality and response to virus infection are collectively taken into consideration.